2019
DOI: 10.1016/j.compstruct.2019.110994
|View full text |Cite
|
Sign up to set email alerts
|

Fire resistance of concrete-filled steel tube columns with preload. Part I: Experimental investigation

Abstract: Preload in a cast-in-situ concrete-filled steel tube (CFST) structure is an important parameter that has been studied and considered in design and construction. However, the impact of a preload on fire resistance of CFST has not been taken into account in the existing design method of CFST under fire. In this paper, twelve CFST columns with and without preload in the steel tubes are experimentally studied to investigate their heating process, failure modes, thermal and structural responses. The test results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…As one of the structural components of CFT structures, CFT columns play an important role in CFT structures systems. Plenty of studies have been conducted on the properties of the CFT column, including compressive behavior [13][14][15], bond behavior [16][17][18][19], seismic performance [20,21], fire resistance [22][23][24], and so on. Meanwhile, numerous different types of concrete have been also used in concrete-filled steel tubes, such as lightweight aggregate concrete [25,26], high-strength concrete [27], recycled aggregate concrete [28][29][30][31][32] and fiber-reinforced plastic (FRP)-confined concrete [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…As one of the structural components of CFT structures, CFT columns play an important role in CFT structures systems. Plenty of studies have been conducted on the properties of the CFT column, including compressive behavior [13][14][15], bond behavior [16][17][18][19], seismic performance [20,21], fire resistance [22][23][24], and so on. Meanwhile, numerous different types of concrete have been also used in concrete-filled steel tubes, such as lightweight aggregate concrete [25,26], high-strength concrete [27], recycled aggregate concrete [28][29][30][31][32] and fiber-reinforced plastic (FRP)-confined concrete [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Concrete-filled steel tube (CFST) structures with virtues of higher bearing capacity [1], greater ductility property [2][3][4], easier construction [5], better seismic performance [6,7] and much more excellent fire-resistant performance [8,9] are widely utilized in high-rise buildings, industrial plants, bridges and underground structures [10][11][12][13][14] recently. With application and popularization of CFST structures, significant economic and social benefits are obtained and a series of technical problems have been solved [2][3][4][5][6][7]15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is meaningful to carry out the investigation on the structural properties of PAC-filled steel tube (PACFST) structures.The CFST column is one of the most widely used structural members in CFST structures. Recently, numerous researches have been conducted on structural properties of CFST columns, typically in compressive behavior [30][31][32], bond behavior [33,34], seismic performance [6,7], fire resistance [8,9,35]. Meanwhile, some design codes have been developed for design of CFST columns by different countries [36][37][38][39][40].…”
mentioning
confidence: 99%
“…Experimental study is generally the preferred method to study a CFST with preload [12,13] and its fireresistance [14][15][16][17] . A more detailed review on relevant experimental studies can be found in the companion paper [24] . It is also essential in the study of fire resistance of CFST to develop a reliable numerical model to replace expensive tests and simulate complex loading and support conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is also essential in the study of fire resistance of CFST to develop a reliable numerical model to replace expensive tests and simulate complex loading and support conditions. As a companion paper of [24] , this paper attempts to study the influence of preload on fire resistance of CFST both numerically and analytically. A finite element model on fire resistance of preloaded CFST, which is valid for both room and elevated temperature, is developed and validated against available test results.…”
Section: Introductionmentioning
confidence: 99%